Vulnerable spaces, unequal responses: lessons for transformative climate resilience in Lagos - Ekoh, Susan S.; Teron, Lemir (Frontiers in Sustainable Cities, 2023)
Urban coastal megacities like Lagos face flooding challenges that may be exacerbated by climate change in the future. Through an urban political ecology lens, this study engages with the dynamics of politics and power that produce differentiated flood impacts and adaptation strategies. Data from telephone interviews of 21 Lagos residents across the mainland and island areas reveal people's understanding of their flood vulnerabilities within the wider socio-political context of Lagos. In particular, state failure in the provisioning of services, amenities, and overall flood protection, shapes flood risk in Lagos. In addition, income and access to material resources inform people's experiences and ability to cope with flooding. Furthermore, citizens apply localized strategies to prepare for and cope with flooding events, particularly through Community Development Associations (CDAs). These localized strategies have implications for transformative resilience. However, these forms of endogenous resilience cannot replace attention to wider urban governance challenges in cities like Lagos.